"Wir laden Sie ein!" - "Jetzt anmelden!" Zur Spannweite von Instruktionen in Werbebriefen - Nielsen, Martin (HERMES - Journal of Language and Communication in Business, 2008)
Instructive texts are an inclusive term for a wide range of action initiating texts, i.e. texts where the action is being initiated through the text (e.g. in a sales letter, Nielsen 2003a: 66), and action commanding texts, i.e. texts where an action which the receiver wanted to execute anyway is being instructed (e.g. instructions, Reiß 1983: 17). Since sales letters are action-initiating and thus as a text genre constituting feature contain directive speech acts (Searle 1969, 1976, Wagner 2001, Nielsen 2006), they are per definition face-threatening (Brown/ Levinson 1978, Nielsen 2006). The communication configuration is asymmetric and the power relationship skewed: On the one hand, the sender wants something from the receiver although not entitled to claim that because of the power relations. On the other hand, the action that the receiver is requested to do might very well be in the interest of the receiver. On that background it seems natural that there is a wide range in the realization of instructions in sales letters: from the euphemistic „We invite you!“ to the completely unhidden, almost rude „Register now!“ This article sets out to describe and explore this range on the basis of authentic Danish and German sales letters and to make an attempt at a first tentative classification of politeness strategies that soften the face-threatening speech acts of those instructions.